THE ACTIVE LEARNING IMPLEMENTATION AND MATHEMATICAL TASKS TO PROMOTE REASONING ABILITIES ON BASIC GEOMETRY OF GRADE 7 STUDENTS - Junthawong, arin; Klin-eam, Chakkrid (Journal of Buddhist Education and Research (JBER), 2023)
The purpose of this research were to study the active learning implementation and mathematical tasks to promote reasoning abilities on basic geometry of grade 7 students. The target group 20 students in Mathayomsuksa 1 at an opportunity expansion school in Phitsanulok Province, semester 2, academic year 2021. The methodology of this research was classroom action research. The research tools were lesson plans, the activity sheets and the reasoning ability test. The data were analyzed by on content analysis. The research found that most of the students have two reasoning abilities, namely analyzing the relationship of the data and explaining conclusions were in a good level.